2008
DOI: 10.1055/s-0028-1087176
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the FTO Gene Influences Food Intake but not Energy Expenditure

Abstract: Polymorphisms in the FTO (fat mass- and obesity-associated) gene are associated with obesity. The mechanisms how genetic variation in this gene influences body weight are unknown. Body weight is determined by energy intake/storage and energy expenditure. In this study, we investigated whether genetic variation in FTO influences energy expenditure or food intake in carefully phenotyped subjects. In 380 German subjects, insulin sensitivity was measured by a hyperinsulinemic euglycemic clamp. Lean body mass and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 21 publications
4
128
0
6
Order By: Relevance
“…The enhancement in obesity risk linked to a high CHO intake may be partly explained by the fact that CHO are not able to activate the PPARG protein and could worsen the action of the Ala12 substitution on the receptor activity. The impact of this rs9939609 SNP of FTO gene on human body weight is mainly through energy intake; however, some results are contradictory (Berentzen et al 2008;Do et al 2008;Speakman et al 2008, Goossens et al 2009Haupt et al 2009). In our elderly population, no effect of FTO on obesity was found.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement in obesity risk linked to a high CHO intake may be partly explained by the fact that CHO are not able to activate the PPARG protein and could worsen the action of the Ala12 substitution on the receptor activity. The impact of this rs9939609 SNP of FTO gene on human body weight is mainly through energy intake; however, some results are contradictory (Berentzen et al 2008;Do et al 2008;Speakman et al 2008, Goossens et al 2009Haupt et al 2009). In our elderly population, no effect of FTO on obesity was found.…”
Section: Discussionmentioning
confidence: 99%
“…FTO is abundantly expressed in the hypothalamus, and epidemiological and functional studies suggested to be directly involved in the regulation of energy intake (Cecil et al, 2008;Haupt et al, 2009). Moreover, FTO is expressed in multiple tissues such as white adipose tissue, skeletal muscle and liver, also having direct influences on adipose tissue metabolism (Grunnet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…6 However, no difference in measured energy expenditure according to FTO genotype has been observed in human studies. [7][8][9] As genetic variation in FTO is associated with fat mass, the A-allele may be related to mortality due to the increase in fatness. However, in a Danish study including 1628 individuals (205 deaths), the A-allele was related to increased mortality that was independent of fatness.…”
Section: Introductionmentioning
confidence: 99%